Characterization and Enzyme Engineering of a Hyperthermophilic Laccase Toward Improving Its Activity in Ionic Liquid - Stevens, Joseph Craig; Rodgers, David W.; Dumon, Claire; Shi, Jian (Frontiers in Energy Research, 2020)
Ionic liquids (ILs) are organic salts molten at room temperature that can be used for a wide variety of applications. Many ILs, such as 1-ethyl-3-methylimidazolium acetate ([C2C1Im][OAc]), have been shown to remove a significant fraction of the complex biopolymer lignin from biomass during pretreatment. Valorizing lignin via biological pathways (e.g., enzymes) holds promise but is limited by the low biocompatibility of many ILs used for pretreatment. The discovery of thermostable enzymes and the application of enzyme engineering techniques have yielded biocatalysts capable of withstanding high concentrations of ILs. Converting lignin from a waste product to value-added chemicals is vital to the success of future cellulosic biorefineries. To that end, we screened the activity of the lignolytic enzyme laccase from a hyperthermophilic bacterium (Thermus thermophilus) in aqueous [C2C1Im][OAc]. Despite the thermophilicity (Topt > 90°C) of this laccase, significant activity loss (>50%) was observed in only 2% (w/v) [C2C1Im][OAc]. Kinetics studies show that the IL can bind to the free enzyme and the enzyme-substrate complex. Docking simulations suggest that the cation favors binding to a region close to the active site. We then used a rational design strategy to improve the activity of the laccase in [C2C1Im][OAc]. A total of 8 single amino acid mutations were made; however, there were no significant improvements in the activity of the mutants in [C2C1Im][OAc] compared to the wild type. The results of this study shed light on the complex nature of enzyme-IL interactions and the challenges faced when designing a biological lignin valorization strategy.